Dual Leadership and Local Policy Implementation: A Case Study of E-Government Implementation in Vietnam - Hung Dao (Indonesian Association for Public Administration, 2026)
This study investigates how dual local leadership—embodied by the Provincial Party Secretary and the Chairman of the Provincial People’s Committee—shapes divergent policy implementation strategies within Vietnam’s party-state governance model. Fo- cusing on the politically sensitive and institutionally novel domain of e-government, this study explores how local cadres adapt implementation strategies over time in response to varying levels of policy clarity and political consensus. Employing a qual- itative comparative case study of three provinces—Hue, Dak Lak, and Ben Tre—char- acterized by different e-government development trajectories and strategic choices, the analysis reveals that interactions between the Party and administrative apparatuses generate distinct degrees of political consensus, which, in turn, influence implementa- tion outcomes. The study identifies four emergent implementation types—Symbolic, Self-Directed, Disjointed, and Sustainable—and introduces the ambiguity–Consen- sus Matrix, a conceptual framework for understanding implementation dynamics in one-party regimes. By illuminating subnational political dynamics and the contingent role of dual leadership, this study contributes to the broader public policy literature on policy implementation in centralized authoritarian systems.